Spanish cinema against itself : cosmopolitanism, experimentation, and militancy - Marsh, Steven, 1963- (New directions in national cinemas., 2020)
Spanish Cinema against Itself maps the evolution of Spanish surrealist and politically committed cinematic traditions from their origins in the 1930s'with the work of Luis BuNuel and Salvador DalI, experimentalist JosE Val de Omar, and militant documentary filmmaker Carlos Velo'through to the contemporary period. Framed by film theory this book traces the works of understudied and non-canonical Spanish filmmakers, producers, and film collectives to open up alternate, more cosmopolitan and philosophical spaces for film discussion. In an age of the post-national and the postcinematic, Steven Marsh's work challenges conventional historiographical discourse, the concept of "national cinema," and questions of form in cinematic practice.